'Toward understanding the nature of history and its limitations': An interview with the American Artist David Schutter. (1st October 2018) - Mieves, Christian
In this conversation American painter David Schutter and the author discuss key aspects of Schutter's work. Schutter (born 1974), whose work makes reference to major European painting collections, explores in his work the relation to tradition and repetition of artistic conventions. His work, presented at 'Documenta 14' (2017), often employs strategies of radical limitation of the colour scheme, and restriction of visibility, sometimes blackening out the image plane altogether. This raises questions about the detachment from the referent object, self-reflexivity and the trope of unrepresentable in contemporary painting in the beginning of the twenty-first century. The conversation will further focus on ways Schutter's work transgresses from a narrow mimetic framework by mitigating in his paintings the difference between original and double and by employing diminished clarity and ambiguity in his work.